2007
DOI: 10.3171/ped.2007.106.6.450
|View full text |Cite
|
Sign up to set email alerts
|

Bandages, dressings, and cranial neurosurgery

Abstract: A total of 702 operations were performed in 577 patients; only five patients received any type of surgical bandaging. There were four SSIs (0.57%; 95% confidence interval [CI] 0.16-1.45). The postoperative infection rate in the 626 clean cases was 0.48% (95% CI 0.10-1.39) and was 2.63% (95% CI 0.07-13.81) in the 38 clean-contaminated cases. The data obtained in this investigation is consistent with the position that bandaging incisional scalp wounds after cranial surgery adds little if any benefit beyond the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These preliminary findings may be associated with the reduction of proritis caused by the presence of residues of blood, disinfectants, and adhesive dressings [28,29].…”
Section: Study End Pointsmentioning
confidence: 88%
“…These preliminary findings may be associated with the reduction of proritis caused by the presence of residues of blood, disinfectants, and adhesive dressings [28,29].…”
Section: Study End Pointsmentioning
confidence: 88%
“…In almost all patients the surgical site was dressed with a standard dressing in line with guidelines (WHO 2016). In around a quarter of the cases, a bandage was used; however, no association has been identified between bandages and SSI reduction or decreased wound healing problems in the literature to date (Winston et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although a study on 702 operations in 577 patients demonstrated that bandaging incisional scalp wounds after cranial neurosurgery did not add any benefit [ 12 ], we prefer using the head bandage to minimize the formation of large hematoma, and probably, subsequent infection, especially fractures in clean-contaminated areas, e.g., involvement of paranasal sinuses. An on-top soft dressing using an elastic bandage or kinesiologic taping was used to improve blood and lymph flow, remove congestion of lymphatic fluid or hemorrhage, and reduce postoperative pain and swelling (and trismus, if the masticatory organs are involved) [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%